الدراسة التحليلية الصرفية عن الأفعال الثلاثية المزيدة في نظم شعب الإيمان: A Morphological and Analytical Study of Augmented Triliteral Verbs in Nuzum Sha‘b al-Iman - Saidah Muniroh; Muhammad Faisol; Ma'rifah Munjiah (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
Shorof (Arabic morphology) plays a crucial role in Arabic grammar by transforming the root of a word into various derived forms to convey precise meanings. These morphological changes are essential for accurate and contextually appropriate communication. As a fundamental branch of Arabic linguistics, the study of shorof enables a deeper understanding of word formation and structural modification, ensuring linguistic accuracy and fluency. This study focuses on analyzing the application of fi‘l tsulāthī mazīd (augmented triliteral verbs) and identifying their errors in the poem Nadzom Syu‘abul Īmān by KH. Zaini Mun‘im, which comprises 314 stanzas. Employing a qualitative descriptive approach, the research gathers data from both primary and secondary sources. The primary data include Nadzom Syu‘abul Īmān, Al-Amtsilah at-Tashrīfiyyah, and Mulakhkhaṣ Qawā‘id al-Lughah al-‘Arabiyyah, while the secondary data consist of relevant literature on augmented triliteral verbs and morphological errors. Data were collected through documentation, reading, and note-taking, and analyzed using Miles and Huberman’s interactive model. The findings reveal 79 instances of fi‘l tsulāthī mazīd distributed across seven awzān (patterns): fā‘ala, fa‘‘ala, af‘ala, ifta‘ala, tafa‘‘ala, infa‘ala, and istaf‘ala. Additionally, 20 errors were identified across these patterns, with varying frequencies depending on the morphological form. يلعب علم الصرف دورًا حاسمًا في النحو العربي من خلال تحويل جذر الكلمة إلى صيغ مختلفة للتعبير عن معانٍ دقيقة ومحددة. وتُعد هذه التحولات الصرفية ضرورية لتحقيق التواصل اللغوي السليم والدقيق في السياق. وباعتباره أحد الفروع الأساسية في علم اللغة العربية، فإن دراسة الصرف تُسهم في فهم أعمق لبنية الكلمة وآليات اشتقاقها، بما يضمن سلامة التعبير والطلاقة اللغوية. يهدف هذا البحث إلى تحليل تطبيق الأفعال الثلاثية المزيدة (fi‘l tsulāthī mazīd) والكشف عن أخطائها في قصيدة نظم شعب الإيمان للشيخ زيني منعم، التي تتكون من 314 بيتًا شعريًا. استخدمت الدراسة المنهج الوصفي النوعي، حيث تم جمع البيانات من مصادر أولية وثانوية. وتشمل المصادر الأولية: نظم شعب الإيمان، وكتاب الأمثلة التصريفية، وملخص قواعد اللغة العربية، بينما تتضمن المصادر الثانوية الدراسات الأدبية واللغوية المتعلقة بالأفعال الثلاثية المزيدة وأخطائها الصرفية. تم جمع البيانات من خلال التوثيق والقراءة الدقيقة وتدوين الملاحظات، ثم تحليلها وفق نموذج مايلز وهوبرمان للتحليل التفاعلي للبيانات. أظهرت النتائج وجود 79 فعلاً ثلاثيًا مزيدًا موزعة على سبعة أوزان صرفية هي: فاعل، فعّل، أفعل، افتعل، تفعّل، انفعل، واستفعل. كما تم تحديد عشرين خطأً صرفيًا ضمن هذه الأوزان، تتفاوت في تكرارها بحسب النمط الصرفي المستخدم.